Influence of poly(3-hydroxybutyrate) addition on the properties of poly(lactic acid) nonwoven obtained by the melt-blown technique - Łatwińska, M.; Sójka-Ledakowicz, J.; Kudzin, M. (Polimery, 2015)
Poly(lactic acid) (PLA) nonwoven and PLA (85 wt %)/P(3HB) (15 wt %) [P(3HB) — poly(3-hydroxybutyrate)] composite nonwoven were obtained using the melt-blown technique. The thermal properties, physical-mechanical parameters, specific surface area and susceptibility to hydrolytic degradation were studied for the obtained nonwovens. DSC analysis indicated noticeable changes in the polymers structure during melt-blowing. The addition of P(3HB) to PLA nonwoven generally downgraded the physical-mechanical properties and caused specific surface area decrease. Both analyzed nonwovens were more susceptible to hydrolysis in alkaline than neutral medium.